2014
DOI: 10.15376/biores.9.2.2949-2959
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CuSO4 Content in the Plating Bath on the Properties of Composites from Electroless Plating of Ni-Cu-P on Birch Veneer

et al.

Abstract: A wood-based composite was prepared via simple electroless Ni-Cu-P plating on birch veneer for EMI shielding. The effects of CuSO 4 ·5H 2 O concentration on the metal deposition, elemental composition, phase structure, surface morphology, wettability, surface resistivity, and shielding effectiveness of coatings were investigated. The coatings were characterized using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and scanning electron microscopy (SEM). When the CuSO 4 ·5H 2 O concentration wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Guangyu Li et al [24] and Hui et al [18] in their studies on electroless coatings over CF/PEEK and Birch veneer respectively had observed a decrease of SE with increasing copper content.…”
Section: Emi Shielding Effectivenessmentioning
confidence: 98%
See 1 more Smart Citation
“…Guangyu Li et al [24] and Hui et al [18] in their studies on electroless coatings over CF/PEEK and Birch veneer respectively had observed a decrease of SE with increasing copper content.…”
Section: Emi Shielding Effectivenessmentioning
confidence: 98%
“…10 dB [18]. From the scattering parameters, the EMI SE is calculated from the equations given below:…”
Section: R -T) Se T Is Expressed As Se T = Se R + Se a ; The Se M Ismentioning
confidence: 99%
“…Therefore, as early as 20 years ago, electroless plating technology was used to prepare electromagnetic shielding wood (Nagasawa et al 1999;Wang et al , 2006; . In the following ten years, the form of wood electromagnetic shielding materials has also been expanded, such as electromagnetic shielding particle board and plywood Hui et al 2013Hui et al , 2014Pan et al 2016;Tang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The physicochemical characteristics of autocatalytic deposits are closely dependent on the composition of the baths and the respective operating conditions. [5][6] Hence, the interest of research performed about the kinetic phenomena arising at the metal/solution interface. [7][8][9] Most of commercially electroless copper baths use (i) formaldehyde, 10 as the reducing agent; (ii) sodium potassium tartrate (called as 'Rochelle salt'), sodium citrate or ethylenediamine tetraacetic acid, as complexing agents; (iii) boric acid as a buffer; (iv) oxygen or thiourea, as additives for stabilising the system; and (vi) cyanide or proprionitrille, as additives for accelerating the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The physicochemical characteristics of autocatalytic deposits are closely dependent on the composition of the baths and the respective operating conditions. 56 Hence, the interest of research performed about the kinetic phenomena arising at the metal/solution interface. 79…”
Section: Introductionmentioning
confidence: 99%